Comparison of Nursing College Students and Other Major College Students Before and After Education on Bioethical Consciousness (Medico Legal Update, 2019)
Background/Objectives: Preliminary health care ethics education is important for improving the ethical values in the field. This study examined the effects of ethics education on college students through various learning methods.Method/Statistical Analysis: This study was an design with an 272 students in the first year of nursing college students of experimental group and 277 students in the first year of nursing college students of control group. Experimental groupwho undertook bioethics education, and control group who did not. The bioethics education was taught using textbooks, PPT, and video materials for two hours per week for 15 weeks. A post-questionnaire survey was conducted to measure the changes in the awareness of bioethics in before and after the training.Findings: The correlation coefficient of 0.335 (p = .000) confirmed the improvement in bioethical consciousness and the necessity of bioethics education for college students. In addition, the correlation coefficient between the necessity of bioethics education in college and the self - ethics of the day was positively correlated with 0.233 (p = .000).Improvements/Applications: These results show that bioethics education is an essential tool in improving bioethics awareness.